HUBUNGAN MOTIVASI DENGAN KINERJA KADER BALITA - Manoppo, Ivanna; Rumambi, Arlinda A (Fakultas Keperawatan, Universitas Klabat, 2022)
Abstract Posyandu is one form of health service to overcome and find nutritional problems in toddlers. If the kader do not carry out their roles properly, the concequence is that the nutritional status of children under five cannot be detected early. The purpose of this study was to determine the relationship between motivation and performance of toddler cader in the working area of the Kema Health Center. The research design used was descriptive correlative with cross sectional approach. Using total sampling technique. The number of research samples was 97 respondents. The results of the frequency and percentage statistical tests showed that 70,1% had high motivation and 29,9% had low motivation. As for the results of the performance of cadres 75,3% had good performance, 23,7% had sufficient performance, 1% had poor performance. The results of the spearmean rank/rho statistical test show p-value=0,707>0,05 which means that there is no significant relationship between motivation and the performance of toddler cadres. Recommended for further researchers it is recommended to look for other factors that affect performance namely knowledge and training.